Comparison Between Contextual and Conventional Learning on The Poetry Writing Ability of Senior High School 1 Lembang Students - Razanah, Marini; Hikmat, Ade; Safi'i, Imam (Perspektif Ilmu Pendidikan, 2024)
Students' ability to write poetry must be more meaningful, this will not happen if Indonesian language teachers still use conventional models in their learning. Breakthroughs such as Contextual Learning are needed so that learning to write poetry is more meaningful for students. The aim of the research is to determine the differences in the poetry writing abilities of students who study using Contextual Learning and conventional models at SMAN 1 Lembang. The research used in this research is experimental, with Non-equivalent (Pretest and Posttest) Control-Group Design. The population in this study was class X students of Senior High School 1 Lembang, totaling 10 classes. The sample was determined randomly, so classes X 3 and X 7 were determined, each with 31 students. The instrument uses the Poetry Writing Ability Test. Data analysis follows the following steps: 1) Normality test with p-value > 0.05, 2) Homogeneity test with p-value < 0.05, and 3) ANOVA test with p-value < 0.05. If the data is not normal or homogeneous then a Non-Parametric test is carried out using the Wilcoxxon and Mann-Whitney U tests. The research results show that the use of Contextual Learning in learning to write poetry provides better results when compared to conventional models.